2, 6, 9-Trisubstituted purines as CRK3 kinase inhibitors with antileishmanial activity in vitro. Issue 11 (1st June 2015) - Řezníčková, Eva; Popa, Alexandr; Gucký, Tomáš; Zatloukal, Marek; Havlíček, Libor; Bazgier, Václav; Berka, Karel; Jorda, Radek; Popa, Igor; Nasereddin, Abdelmajeed; Jaffe, Charles L.; Kryštof, Vladimír; et al.
Graphical abstract: Abstract: Here we describe the leishmanicidal activities of a library of 2, 6, 9-trisubstituted purines that were screened for interaction with Cdc2-related protein kinase 3 (CRK3) and subsequently for activity against parasitic Leishmania species. The most active compound inhibited recombinant CRK3 with an IC50 value of 162 nM and was active against Leishmania major and Leishmania donovani at low micromolar concentrations in vitro. Its mode of binding to CRK3 was investigated by molecular docking using a homology model.